2010
DOI: 10.1002/hep.23572
|View full text |Cite
|
Sign up to set email alerts
|

Acetate, the key modulator of inflammatory responses in acute alcoholic hepatitis

Abstract: Acute alcoholic hepatitis is characterized by disproportionate macrophage inflammatory cytokine responses to bacterial lipopolysaccharide. Lack of knowledge of the underlying mechanism has limited progress toward effective therapy. We postulated a novel mechanism by which ethanol increases histone acetylation, increasing proinflammatory gene transcription and cytokine synthesis. Cytokine responses to lipopolysaccharide in a human macrophage cell line cultured in 86 mM ethanol, 1 mM acetate, and normal media we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 146 publications
4
104
1
1
Order By: Relevance
“…It is also of interest to note that acetate supplementation inhibited HDAC activity in brain (Soliman and Rosenberger, 2011). Acetate is also a modulator of inflammatory responses (Kendrick et al, 2010). The literature evidence and results presented here support the view that ethanol itself activates histone acetyltransferase, whereas acetate inhibits HDAC.…”
Section: Discussionsupporting
confidence: 79%
“…It is also of interest to note that acetate supplementation inhibited HDAC activity in brain (Soliman and Rosenberger, 2011). Acetate is also a modulator of inflammatory responses (Kendrick et al, 2010). The literature evidence and results presented here support the view that ethanol itself activates histone acetyltransferase, whereas acetate inhibits HDAC.…”
Section: Discussionsupporting
confidence: 79%
“…However, ethanol metabolism is itself a potent source of reactive oxygen species, which may impair the ability of the glucocorticoid receptor to recruit HDACs to ''switch off'' transcription of proinflammatory genes by the same mechanism. Alternatively, we have recently demonstrated that the increased concentrations of free acetate generated by ethanol metabolism favor increased histone acetylation and enhanced proinflammatory gene expression in a cell-line model of AAH, 19 and this mechanism could antagonize the normal glucocorticoid effect.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent neutrophils exposed to acetate undergo global inhibition of HDAC activity (Vinolo et al, 2011). Treatment with 1 mM acetate significantly reduces the HDAC activity and increases global histone acetylation in human macrophages, corresponding to a decrease in inflammatory cytokine [interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-a] production (Kendrick et al, 2010). Conversely, human gastric adenocarcinoma (AGS) cells treated with sodium acetate for 24 h showed increased mRNA and protein levels of IL-1β, IL-8, and TNF-α.…”
Section: Introductionmentioning
confidence: 99%